The HISTRA digital platform: Research on HIStory of TRAnslation - Cristina Gómez Castro; María Jesús Vallejo Fernández (Chronotopos)
HISTRA (HIStory of TRAnslation in Spanish) aims to transfer to an electronic resource a bulky archive of file cards manually compiled by Dr. Santoyo, an expert in the field of Translation History, who registered bibliographical references of Spanish translations of English works from the 16th century until the 1980s. This process has been carried out with the help of the tool entitled Koha-Kobli, an integrated system for library management, free and open source software carried out by the Grupo de Trabajo de las Bibliotecas de la Administración General del Estado. The work methodology guarantees an exhaustive bibliographic account of the references included and normalization of the registers, based on the Reglas de Catalogación, using the international format MARC21. HISTRA constitutes a robust platform for the retrieval of relevant information about translators and translated works, thus contributing to research in translation history, facilitating studies on literary reception of works translated from English into Spanish, authors and translators.